The Relevance of Islamic Values in the English Curriculum: A Life Skills Approach as a Means of Character Building - Kasman, Kasman; Siregar, Syamsiah Depalina; Pohan, Ali Jusri (Al-Mudarris, 2024)
This study aims to explore the relevance of Islamic values in the English curriculum through a life skills approach as a means of character building. In the context of globalization, character education has become one of the main focuses in curriculum development. This research uses a qualitative approach with a case study method that involves analyzing curriculum documents, in-depth interviews with educators, and classroom observations in several senior high schools in Indonesia. The results show that the integration of Islamic values in English learning can enrich the learning content and have a positive impact on students' character development. Values such as honesty, hard work, and responsibility can be internalized through learning materials that are relevant to daily life. In addition, the life skills approach allows students to apply these values in practical situations, improving their social and emotional skills. This research found that teachers play a crucial role in implementing this approach, requiring adequate training and support. In conclusion, the Islamic values-based life skills approach in the English curriculum is not only relevant, but also effective in shaping students' character with integrity and nobility. The implications of this research point to the importance of developing educational policies that support the integration of religious values in the national curriculum.